0484 Individuals with Obstructive Sleep Apnea have Higher Likelihood of Multiple Involuntary, Job Losses. (12th April 2019) - Bautista, Jose R; McMorrow, Taryn E; Silva, Graciela; Haynes, Patricia L; Bell, Melanie L; Quan, Stuart F
Abstract: Introduction: Involuntary job loss can be related to both employer and personal factors. Irrespective of cause, it is likely to cause negative changes in daily activities and sleep patterns. Obstructive sleep apnea (OSA) can impair mental and physical performance and thus may be an etiologic factor leading to job loss. We hypothesized that people with OSA were more likely to have a history of multiple job loss (HMJL). Methods: Participants with data regarding demographic and physical characteristics, employment history, and results from an out of center sleep test were selected from the ongoing, prospective Assessing Daily Activity Patterns through occupational Transitions (ADAPT) study. A propensity score analysis was performed to investigate the association between the presence of OSA and having a HMJL. OSA was defined as an apnea hypopnea index (AHI) of > 15/hour (moderate-to-severe OSA). The propensity model used age (years), sex (male/female), race/ethnicity (white/non-white), whether a participant usually began their work shift between 7-9am (yes/no), whether they worked in a social environment (management, healthcare, or sales) or non-social (all other job categories), and payment type (hourly/salary) as predictors of OSA. Post matching, a logistic regression model was fitted on the matched data using HMJL as the response and OSA as the predictor. Results: A total of 261 participants were used for the propensity score analysis. After propensity score matching a total of 39 matched pairs (N = 78) remained. From the logistic regression model on the matched data, the odds of having a HMJL for those with OSA was 2.86 (95% CI: [1.16 - 7.32]). Conclusion: Individuals with moderate-to-severe OSA were more likely to have experienced multiple involuntary job losses. Body mass index (BMI) data were not collected and the inability to include BMI in the model is considered as a limitation, given the estimated relationship between BMI and job loss. Despite this limitation, these data provide valuable, proof of concept that moderate-to-severe OSA may confer significant long-term occupational and economic consequences that are uniquely associated with involuntary job loss. Support (If Any): #1R01HL117995-01A1.